2018
DOI: 10.1080/14397595.2017.1422232
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disease activity and patient-reported outcomes in rheumatoid arthritis: Post hoc analyses of overall and Japanese results from two phase 3 clinical trials

Abstract: Remission/LDA were associated with improvements in PROs in overall and Japanese patient populations; however, some patients achieving remission had residual symptoms, including pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The impact of RA on patients has been described in several studies that concluded RA causes major and diverse effects on patients, affecting both physical and mental domains of well-being [ 18 , 19 ]. A reduction in disease activity results in improvement of patients’ physical function and health-related quality of life [ 20 ]. Consistent with improvements in disease activity, patient-reported outcomes including physical function assessment (HAQ-DI), quality-of-life domains (SF-36) and severity of morning stiffness scores significantly improved among patients treated with upadacitinib compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of RA on patients has been described in several studies that concluded RA causes major and diverse effects on patients, affecting both physical and mental domains of well-being [ 18 , 19 ]. A reduction in disease activity results in improvement of patients’ physical function and health-related quality of life [ 20 ]. Consistent with improvements in disease activity, patient-reported outcomes including physical function assessment (HAQ-DI), quality-of-life domains (SF-36) and severity of morning stiffness scores significantly improved among patients treated with upadacitinib compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Residual pain and impaired function persist in many patients with RA despite the achievement of disease control [4,5,24]. This residual pain may be non-inflammatory in origin, caused by sensitisation of nociceptors or peripheral joint damage; or it may be due to central sensitisation [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…However, achieving this objective target is not always associated with a corresponding improvement in disability (Health Assessment Questionnaire (HAQ)) scores and other patient-reported outcomes (PROs): In a study of the Leiden Early Arthritis Clinic cohort, for example, patients with RA were now diagnosed after a shorter duration of symptoms and with less inflammation than they were 20 years ago, but HAQ results remained stable over this time while PROs worsened [3]. Indeed, residual pain and functional impairment can persist despite ongoing treatment and can negatively affect quality of life [4,5]. Control of pain and maintenance of physical function are priorities for patients with RA [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…PtGA, PhGA, and other clinical measures are shown at baseline, Week 12, and Week 24 in Supplementary Tables S1 and S2. Note: the baseline characteristics in Table 1 are also disclosed in a related manuscript [17] describing the results of a separate post hoc analysis of data from RA-BEAM and RA-BEGIN.…”
Section: Baseline Characteristicsmentioning
confidence: 99%